Jewish Theatre Making in Mantua, 1520-1650 - Jaffe-Berg, Erith (Jewish Engagements Ser., 2022)
This book studies how the Jewish community of Mantua established, normalized, and maintained interrelations with the Christian community for over 130 years, from 1520 to 1650, by means of theatre performance for the Gonzaga Dukes. Performance is shown to have been a mutually beneficial ""currency"" that both the Dukes and Jews could use to calibrate their relations with one another. Seen in this light, the author demonstrates that performance was not the conse.